2001
DOI: 10.4269/ajtmh.2001.65.90
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax clinically resistant to chloroquine in Colombia.

Abstract: Abstract. Chloroquine-resistant Plasmodium vivax has been the subject of numerous case reports and prospective studies from Oceania and Asia. In contrast, only case reports exist from the Americas. We performed a prospective study with 28-day follow-up of clinical responses to chloroquine in 2 P. vivax-endemic regions of Colombia. Three (11%) of 27 patients failed to respond to treatment with the standard regimen of chloroquine (1,500 mg of base over 3 days). One patient demonstrated RI resistance on Day 26; o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
64
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 15 publications
1
64
0
8
Order By: Relevance
“…This is in part a consequence of a perception of the importance of antimalarial drug resistance with P. vivax, compounded by difficulties in standardizing a field-based assay. Over the last decade, a number of clinical studies have demonstrated the emergence of highgrade chloroquine resistance in Papua, Indonesia, and Papua, New Guinea (1,18,21), and its spread to other regions of Asia (6) and South America (20). However, assessment of the clinical efficacy of antimalarial drugs against P. vivax infection is confounded by the occurrence of both reinfections and relapses, making the attributable fraction of recurrent infections due to intrinsic parasite resistance difficult to gauge (2,3,10).…”
mentioning
confidence: 99%
“…This is in part a consequence of a perception of the importance of antimalarial drug resistance with P. vivax, compounded by difficulties in standardizing a field-based assay. Over the last decade, a number of clinical studies have demonstrated the emergence of highgrade chloroquine resistance in Papua, Indonesia, and Papua, New Guinea (1,18,21), and its spread to other regions of Asia (6) and South America (20). However, assessment of the clinical efficacy of antimalarial drugs against P. vivax infection is confounded by the occurrence of both reinfections and relapses, making the attributable fraction of recurrent infections due to intrinsic parasite resistance difficult to gauge (2,3,10).…”
mentioning
confidence: 99%
“…In Brazil, the first clinical evidence was reported in 2000 in Manaus (13). In Colombia, P. vivax CR was described in three cases among 27 subjects (14), and in Peru four cases were confirmed among 177 subjects (15). In 2007, the proper 28-day follow-up of 109 patients with P. vivax prescribed only CQ (PQ prescription was postponed to day 28) led to the confirmation of 10.1% resistance after plasmatic CQ dosage (16).…”
mentioning
confidence: 99%
“…The emergence of resistance to CQ and the failing efficacy of PQ regimens in preventing relapses have raised great concerns in the control of P. vivax malaria. 9,10 Clinical CQ-resistant (CQR) P. vivax was first reported from Papua New Guinea in 1989, 11,12 followed by multiple reports from Indonesia, [13][14][15] Myanmar, 16,17 India, 18,19 Guyana, 20 Brazil, 21,22 Colombia, 23 and more recently in Ethiopia 24 and South Korea. 25 Continued surveillance of P. vivax drug resistance may detect CQR P. vivax parasites in most of its geographic range.…”
Section: Introductionmentioning
confidence: 99%